THE IMPORTANCE OF PREVENTIVE MONITORING MECHANISM ON REPLACEMENT OF PASSPORT DUE TO FORCE MAJEURE - Muhammad Alvi Ghazy; Tony Mirwanto (Journal of Law and Border Protection, 2020)
The mobility of the world's population in the era of globalization has an impact on a country, both positive and negative. Each country must respond carefully so that it does not cause losses to various sectors, one of which is the economic sector and the relationship between countries which can be stretched. Therefore, it is necessary to control the traffic that enters and leaves a country. In minimizing activities that violate the traffic flow of people in the world, especially in Indonesia, laws and regulations that ensure legal certainty protect, respect and declare the human rights of an individual is needed. This can be seen in the implementation and application of many laws in Indonesia, for example the implementation of the immigration law. In its application, the application and application of the immigration law in Indonesia leads to better things than before, including in matters relating to a force majeure.